Experience of overcoming the stereotype of masculinity in Singaporean elite level male gymnasts - Ilma Nur Jannah Fadzal (2018)
The purpose of this study was to provide detailed accounts of the experiences faced by elite male gymnasts in overcoming stereotypes prior and post-entry into gymnastics using phenomenological interviews. Semi-structured interviews were conducted with five Singaporean elite level male gymnasts from the Singapore Gymnastics Association and were transcribed verbatim before being analysed into raw themes, categories and general dimensions. Prior-entry into gymnastics, participants reported the initial exposure of gender stereotypes in the realm of sports. Masculinity was revealed to be a constructed and learned concept after being socially exposed to different cultures, roles and norms. After overcoming societal expectations post-entry into gymnastics, participants exhibited very personalized views on the construct of gender and masculinity despite being aware of the established norms upheld in society. The acceptance of identity was manifested through the encapsulation of masculinized traits that reinstated conformity to society’s definition of masculine, despite the possession of personalized views on gender constructs. The study provides a significant contribution to the concepts of sport and masculinity, through its investigation of Singaporean elite gymnasts within Singapore. The positive experiences can be used as a benchmark to incorporate and promote gender fluidity whereas negative experiences can be used as a platform for future changes of gender stereotypes in the realm of sports.